2006
DOI: 10.1097/01.aog.0000196503.78126.62
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Pregnancy Risk With Assisted Reproductive Technology Procedures

Abstract: II-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
179
1
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(209 citation statements)
references
References 17 publications
21
179
1
8
Order By: Relevance
“…This is a percentage of about 8.95% TEPs/pregnancies in comparison to IVF-ET cycles caused by other factors of infertility (0.75%/PR in our control group; 1.3% [14] up to 18.7%/PR [15] depending on the different assisting reproduction methods applied [16,17]). …”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…This is a percentage of about 8.95% TEPs/pregnancies in comparison to IVF-ET cycles caused by other factors of infertility (0.75%/PR in our control group; 1.3% [14] up to 18.7%/PR [15] depending on the different assisting reproduction methods applied [16,17]). …”
Section: Resultsmentioning
confidence: 60%
“…Numerous investigations deal with "tubal factors" as a common reason for sterility and as an affecting factor on the rate of Ectopic Pregnancies [9]. No data are available on IVF-ET patients, who had a treated TEP prior to an IVF-ET treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have not found an association [95], others have alluded to endometriosis as a possible contributing factor for the occurrence of ectopic pregnancies with implicated pathophysiological mechanisms such as abnormal ciliary beat frequency or abnormal tubal peristalsis [96][97][98].…”
Section: Endometriosismentioning
confidence: 99%
“…The incidence in the general population is approximately 2 % [1]; however a significant increase has been reported after the use of In-Vitro Fertilization (IVF), ranging from 2.1 to 8.6 % [2,3].…”
Section: Introductionmentioning
confidence: 99%